Design and development of a circular disc type efficient automatic decorticator for Charoli (Buchanania lanzan). Issue 12 (22nd April 2022) - Nishad, Praween; Singh, Jaspal; Naik, Rajesh Kumar; Patel, Shadanan; Mangaraj, Shukadev; Mishra, Niraj; Thakur, Rajeev Ranjan
Abstract: The manual decortication process of charoli seeds by beating the dried seeds on the ground with a hand hammer or stone and, by domestic grinder is a laborious, inefficient, time‐consuming as well as uneconomical process. Therefore, an attempt has been taken toward the automation of the charoli decortication process. The decorticator performance was evaluated at three levels of disc speeds, disc clearances, and different moisture levels of charoli seed viz. 197, 246, and 286 rpm; 6, 7, and 8 mm; and 7.83, 8.57; and 9.04% wb, respectively. The selected input parameters were optimized by using the response surface methodology (RSM). The optimum value of disc speed, disc clearance, and seed moisture content was found to be 197 rpm, 7 mm, and 9.04% (wb), respectively. The corresponding response values in terms of decorticating efficiency, whole kernel, and broken kernel percentage at optimum conditions were recorded as 92.5, 21.6, and 3%, respectively. Novelty impact statement: The decorticating capacity of the developed decorticator was found to be 70 kg per hour which was higher than the existing decorticator. Since the developed machine was automatically operated and each unit operation was sequentially and continuously carried out with no manual intervention, the ideal time in each decortication step was absent and subsequently, higher capacity was achieved. The efficiency of the decorticator was found to be 92.5%. The higher capacity and kernel recovery with no human drudgery and lower cost of decortication imply the significance of the development of the machine.